DEBATING THE IMPACT OF DOCTORAL RESEARCH ON THE FUTURE OF NURSING - Ehlers, V (South African Journal of Higher Education, 2016)
A university’s major obligations are to teach, to do research and to provide community service. Doctoral programmes should prepare nurse leaders for the academic, service and policy-making sectors. In order to be awarded a doctoral degree by most universities, the candidate needs to satisfy the examiners that his or her thesis has made a unique and original contribution to nursing and/or health sciences. The impact of these ‘unique and original contributions’ on nursing, healthcare services and policies should be examined. Presenting the research findings in academic and in popular publications and at conferences should help to disseminate the findings. However, the implementation and evaluation of studies’ recommendations should also be realised to impact on the future of nursing.